b y Jonah Winter ; illustrations by Ana Juan. - Winter, Jonah; Juan, Ana (New York : Scholastic, 2007)
Illustrations and simple text describe the life of artist Magdalena Carmen Frida Kahlo, discussing how she learned to paint, how painting saved her life, and why her work is so unique.
Text in Arabic.
K-3
Translation of: Frida.
Title supplied by OCLC WorldCat.
Keywords: Kahlo, Frida -- Juvenile literature; Painters -- Mexico -- Biography -- Juvenile literature; Women artists -- Mexico -- Biography -- Juvenile literature; Kahlo, Frida; Artists -- Mexico; Painters -- Mexico; Arabic language materials; Women -- Biography; Kahlo, Frida; Artists -- Mexico -- Biography; Painters -- Mexico -- Biography; Arabic language; Women -- Biography